Perancangan Aplikasi Manajemen Persediaan Barang di Perusahaan Pengelola Jaringan Akses Telekomunikasi Menggunakan Unified Modelling Language dan Prototyping - Purba, Mariana; Dianing Asri, Sri; Ghufron, Akhmad; Umilizah , Nia; Iryani, Lemi (JSAI (Journal Scientific and Applied Informatics), 2024)
Managing inventory in a telecommunications access network management company is very important because applications with good data management effectively increase the chances of success and maximize profits for the company. In addition, proper inventory data management is essential for identifying new market opportunities, forecasting risks, and understanding market trends. This study aims to clarify the design of inventory applications in accordance with the problems that exist at PT. XYZ is owned by the government as a case study location based on minimum service standards (SPM). This design uses unified modelling language (UML) such as use cases, activity diagrams, class diagrams and prototyping models to support the development of inventory applications in telecommunications access network management companies. The inventory management application in the telecommunication access network management company provides features for admins / users in processing supplier data, incoming goods data and outgoing goods data, and printing monthly reports on inventory of goods